2018
DOI: 10.1038/s41598-018-33569-7
|View full text |Cite
|
Sign up to set email alerts
|

Choosing appropriate prosthetic ankle work to reduce the metabolic cost of individuals with transtibial amputation

Abstract: Powered ankle prostheses have been designed to reduce the energetic burden that individuals with transtibial amputation experience during ambulation. There is an open question regarding how much power the prosthesis should provide, and whether approximating biological ankle kinetics is optimal to reduce the metabolic cost of users. We tested 10 individuals with transtibial amputation walking on a treadmill wearing the BiOM powered ankle prosthesis programmed with 6 different power settings (0–100%), including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 44 publications
(58 reference statements)
0
18
1
Order By: Relevance
“…Ankle-foot work decreased by about 0.036 J/kg from the subject’s lowest stiffness to the highest stiffness, but this decrease only amounted to about a 3% decrease in metabolic cost. Previous studies that have modulated the amount of ankle work may suggest that a greater change in work may be needed to see a large change in metabolic energy [24, 31, 58]. Contrary to our findings, Caputo et al used a powered prosthesis and found that for a work decrease of about 0.03 J/kg, there would be an increase of about 0.148 W/kg in metabolic cost [31].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Ankle-foot work decreased by about 0.036 J/kg from the subject’s lowest stiffness to the highest stiffness, but this decrease only amounted to about a 3% decrease in metabolic cost. Previous studies that have modulated the amount of ankle work may suggest that a greater change in work may be needed to see a large change in metabolic energy [24, 31, 58]. Contrary to our findings, Caputo et al used a powered prosthesis and found that for a work decrease of about 0.03 J/kg, there would be an increase of about 0.148 W/kg in metabolic cost [31].…”
Section: Discussioncontrasting
confidence: 99%
“…The metabolic cost did decrease by about 7 to 8% from the highest to the medium stiffness, which had about a 2.6 J difference in push off work (0.035 J/kg for a 75 kg person) [24]. In a study with a commercially-available powered prosthesis, the prosthetist-chosen power setting was a mean ankle work of 0.11 ± 0.06 J/kg, but the best power setting for decreasing metabolic cost (by about 8.8% ± 4.6%) was 0.24 ± 0.07 J/kg [58]. Therefore, our differences in ankle-foot work between stiffness conditions may not have been large enough to influence the metabolic cost.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in individuals with lower limb amputation, metabolic energy associated with walking is known to be much higher than the ablebodied population and powered prostheses are designed to reduce this burden on their users. (34,35) However, the current gold standard for measuring energy consumption is open-circuit spirometry which is a time-consuming process and requires a user to be tethered to a machine(36). While metabolic cost does play an important role in a person's gait quality, studies have shown that individuals may optimize their gait for a combination of metabolic cost and other factors (37), which could include stability, speed, comfort, or esthetics.…”
Section: Resultsmentioning
confidence: 99%
“…This could be an argument for personalized controllers since prosthesis assistance is learned based on observed human-robot responses, which may resolve the problems that K3 ambulators have in learning to use a powered prosthesis. Another study found that, for all ten individuals with unilateral transtibial amputation included in the experimental protocol, the best tested power setting for the BiOM prosthesis (BiOM T2 Ankle, BionX Medical Technologies Inc., Cambridge, MA) was consistently higher than the prosthetist-chosen setting [13]. This resulted in a statistically significant difference in metabolic cost between the best tested and prosthetist-chosen power settings.…”
Section: Introductionmentioning
confidence: 99%